A Pressure Responsive Artificial Interphase Layer of BaTiO3 against Dendrite Growth for Stable Lithium Metal Anodes. Issue 8 (13th May 2022) - Li, Zhuo; Yu, Rui; Gui, Siwei; Yang, Hui; Guo, Xin
Abstract: Development of lithium (Li) metal anodes in high‐energy‐density batteries is considerably impeded by uncontrolled dendrite growth, side reactions, and related volume changes. In this work, a pressure responsive artificial interphase layer of piezoelectric BaTiO3 (BTO) is constructed on Li anodes to prevent the formation of Li dendrites. Once protruding Li buds compress the interfacial space, the extruded piezoelectric layer generates an internal electric field to effectively change the local electric field around the bud tips, thus promoting homogeneous plating/stripping of Li. The artificial interphase layer not only offers a physical protection to the Li anode, but also helps to regulate the Li flux at the Li/electrolyte interface, which then leads to the uniform Li deposition. Consequently, the BTO‐protected Li anode exhibits stable cycling and small polarization in both Li||Li and Li||Cu cells. When paired with S, LiFePO4 and Ni‐rich high‐voltage cathodes, the Li‐metal batteries also exhibit improved cycling stability and high Coulombic efficiency. Abstract : A pressure responsive artificial interphase layer of piezoelectric BaTiO3 is constructed on the Li anode to direct a uniform Li‐ion flux, consequently, tips of the Li buds are leveled out, preventing the formation of the lithium dendrites by blocking the evolution of the Li buds at the initial stage.